2009
DOI: 10.1074/jbc.m109.006817
|View full text |Cite
|
Sign up to set email alerts
|

A Role for HSP70 in Protecting against Indomethacin-induced Gastric Lesions

Abstract: A major clinical problem encountered with the use of nonsteroidal anti-inflammatory drugs (NSAIDs), such as indomethacin, is gastrointestinal complications. Both NSAID-dependent cyclooxygenase inhibition and gastric mucosal apoptosis are involved in NSAID-produced gastric lesions, and this apoptosis is mediated by the endoplasmic reticulum stress response and resulting activation of Bax. Heat shock proteins (HSPs) have been suggested to protect gastric mucosa from NSAID-induced lesions; here we have tested thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 49 publications
4
53
0
Order By: Relevance
“…Interestingly, GGA, a leading anti-ulcer drug on the Japanese market, has been reported to be an HSP inducer, up-regulating various HSPs not only in cultured gastric mucosal cells but also in various tissues in vivo (41). It was reported that GGA suppresses not only gastric lesions but also lesions of the small intestine, inflammatory bowel disease-related experimental colitis, and neurodegenerative diseases (39,40,46,47). On the other hand, the use of HSP70 inducers in cosmetics -1) (B).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, GGA, a leading anti-ulcer drug on the Japanese market, has been reported to be an HSP inducer, up-regulating various HSPs not only in cultured gastric mucosal cells but also in various tissues in vivo (41). It was reported that GGA suppresses not only gastric lesions but also lesions of the small intestine, inflammatory bowel disease-related experimental colitis, and neurodegenerative diseases (39,40,46,47). On the other hand, the use of HSP70 inducers in cosmetics -1) (B).…”
Section: Discussionmentioning
confidence: 99%
“…A PPI was administered 30 min before indomethacin administration: omeprazole (30, 100 mg/kg), lansoprazole (30, 100 mg/kg), or rabeprazole (30, 100 mg/kg). The following were administered twice-30 min before and 6 h after indomethacin administration: an H 2 receptor antagonist (famotidine (3, 10 mg/kg), cimetidine (100 mg/kg), lafutidine [50] (30 mg/kg), or roxatidine [51] (60, 100, 200 mg/kg)); a mucosal protective agent (teprenone [52] (100, 300 mg/kg), rebamipide [53] (100, 300 mg/kg), irsogladine [54] (1, 10 mg/kg), ecabet sodium [55] (300 mg/kg)); sucralfate (500 mg/kg) or a PG analog (misoprostol (0.1 mg/kg)).…”
Section: Prevention and Treatment Of Small Intestinal Mucosal Injury mentioning
confidence: 99%
“…Because stressor-induced tissue damage is involved in various diseases, HSPs and HSP inducers have received much attention for their therapeutic potential. For example, we have shown using transgenic mice that HSP70 protects the gastrointestinal tract from development of gastric and small intestinal lesions and inflammatory bowel disease (17)(18)(19)(20). Interestingly, geranylgeranylacetone, a leading anti-ulcer drug on the Japanese market, has been reported to be a nontoxic HSP-inducer, up-regulating various HSPs not only in cultured gastric mucosal cells but also in various tissues, including the gastric mucosa in vivo (21).…”
mentioning
confidence: 99%